Respuesta :
[tex] 0 = 4x^2+2x- 1 [/tex]
Quadratic formula is
[tex] x = \frac{-b+-\sqrt{b^2-4ac}}{2a}[/tex]
'a' is the coefficient of x^2 = 4
'b' is the coefficient of x = 2
'c' is the constant = -1
Now we plug in all the values in quadratic formula
[tex] x = \frac{-b+-\sqrt{b^2-4ac}}{2a} [/tex]
[tex] x = \frac{-2+-\sqrt{2^2-4(4)(-1)}}{2(4)} [/tex]
[tex]x = \frac{-2+-\sqrt{18}}{8}[/tex]
The above one is the substitution of values of a,b,c in quadratic formula.
Answer:
Step-by-step explanation:
Its Option A for those who didn’t get the explanation.